PURWARUPA SMART SYSTEM MONITORING PRODUKSI TELUR AYAM BERBASIS INTERNET OF THINGS (IOT) - Siti Maesaroh; Fajar Firmansyah; Yanti -; Willy Muhammad Fauzi (Power Elektronik : Jurnal Orang Elektro, 2023)
In 2020, eggs entering West Java were 587 201.77 eggs and continued to decrease until 2021 as many as 573 012.00 eggs. Chicken eggs are one of the food needs that are much sought after by the public. Not only from the benefits of chicken eggs which provide highly nutritious food substances but also in terms of relatively cheap prices compared to other animal products, the demand for chicken eggs will tend to continue to increase. However, chicken egg breeders in several areas still have difficulty controlling the production of chicken eggs on their farms, one of which is in Tasikmalaya City. Chicken egg production that is not well controlled, causes production to not spread evenly in distribution because the supply of chicken eggs is sometimes erratic. To find out the amount of chicken egg production, breeders are required to directly supervise the production of chicken eggs by going to their cages or farms Based on this description, it is also possible to carry out research on similar matters regarding the development of technology in other animal husbandry sectors which at the same time can provide solutions to the above problems. Research on the use of microcontroller technology can be one of the solutions in monitoring as well as calculating and predicting the amount of chicken egg production in farms so that chicken egg production can be controlled more easily and efficiently.